The Effect of Banana Peel Compost on the Growth and Yield of Spring Onion in Alluvial Soil - ANGELINA ANGELINA; SITI HADIJAH; DINI ANGGOROWATI (Fakultas Pertanian Universitas Tanjungpura, 2018)
The Effect of Banana Peel Compost on the Growth and Yield of Spring Onion in Alluvial SoilAnggelina1, Siti Hadijah2, Dini Anggorowati3 1Agriculture; Faculty University of Tanjungpura2Agriculture; Faculty University of Tanjungpura3Agriculture; Faculty University of Tanjungpurae-mail*anggelina.lina888@gmail.com ABSTRAKSpring Onion (Allium fistulosum L) is one of prospective horticultural crops, which can be cultivated intensively in West Kalimantan. Alluvial soil is the soil type that can be used to cutivate this crop. However, this soil type should be enriched with organic compost, such as compost which was made of banana “Kepok” feel, in order to improve the soil structure, which then can help to increase the growth of onion spring. This treatment expected to make the soil structure be more optimum for the plant root development and growth. This research aimed to determine the best dosage of banana peel compost for the growth and yield of onion spring on alluvial soil. This research has been conducted at the Faculty of Agriculture, Tanjungpura University, from December 20th, 2017 to January 31st, 2018. This research has been designed in a Completely Randomized Design (CRD). The treatment was set in 5 level doses of banana peel compost, with 5 replications, which were P0 = without compost, P1= 250 g compost/polybag or equal to 10 ton compost/ha, P2 = 375 g compost/polybag or equal to 15 tons/ha, P3 = 500g compost/polybag or equivalent 20 tons/ha, and P4 = 625 g compost/polybag or equivalent to 25 tons/ha. The observed variables in this study were plant height, number of leaves, number of tillers, root volume and fresh weight of the plant. The results showed that application of banana peel compost on alluvial soil showed good response significantly to the plant height variable, but showed an average good response to the other observed variables of leaf numbers, number of seedlings, root volumes and fresh weight of the plant.Keywords: Alluvial, Banana peel, Compost, Spring Onion